Controlling A Robot Car Using Android Application Universitas Muhammadiyah Surakarta - Mustafa, Hisham Atef; , Dedi Ari Prasetya,ST (2016)
CONTROLLING A ROBOT USING ANDROID APPLICTION Abstract The Android Operating System is one of the biggest number in usage operating system in the smartphone that also commonly known in our life, for order of entertainment, invention, research, social etc, meanwhile for the research purpose there are many ways those can be done to invent a product to be researched. The objective of this research is to develop a program or an Android application to control a robot powered by Arduino using a motor driver and a Bluetooth modem. The process involved in building the robot includes the assembling of a chassis used for the robot, programing the Arduino as well as the interface for the Android device. This thesis document contains the design of process for the robot and programming for the android interface. The details in the research give the information about the different aspects of computing involved in the whole project. The advantages those might be obtained are the cheap research cost because in the other hand Arduino and Android are open source. The outcome of the project is a combination of embedded computing and programming, the researcher used APP Inventor2to integrate Arduino with Android, based on the test methods it can be concluded that it is easy to implement Arduino with android the Keywords: Android, Arduino, Bluetooth shield, embedded computing